Detection of Toxicity of heavy metal pollution in soils based on their respiratory activity in native soils and simulated substrates (a case-study of the protected area “YAMSKAYA steppe”) - N. O. Bakunovich; O. S. Khokhlova; T. N. Myakshina; A. V. Rusakov; A. S. Shapovalov (Бюллетень Почвенного института им. В.В. Докучаева)
The area “Yamskaya Steppe” of “Belogorye” preserve is located in Belgorod Oblast near the concentration of mining factories: Lebedinskiy and Stoylenskiy mining and concentration complex (MCC), complexes of “KMA-ore” and Oskol metallurgical, TPP etc. Taking into account that the “Yamskaya Steppe” is a SPNR and along with that bears a significant technogenic burden, it is necessary to investigate the properties of dominating soils and to provide the assessment of its contamination by heavy metals (HM). The main purpose of the work was to assess the toxicity of contamination of the soils of “Yamskaya Steppe” by HM in correlation to the investigated respiration activity of microorganisms of native soils of monitoring areas (MA) and artificially created mixes of soils with the dust from shops of factories, containing high concentrations of HM. The investigation of the native soils did not show the correlation of the basal respiration and the type of the soil. However weak and single case showed the correlation of basal breath and the type land use. Only in two soils of the whole 21 soils from the investigated MA the signs of disturbance of functioning of microbial community were revealed. The measurement of the bulk forms of HM showed relative increase in concentrations of Сu, Zn, Zr, Sn, Pb, As on these MA. The experiments with artificial mixtures allowed us to conclude that the implementation of the dust with HM, taken from the shops of Lebedinskiy MCC, affect the microbial activity. That causes the intensification of СО2 emission as incase of measuring of basal respiration rate and in case of substrata-induced respiration. However, that impact might be possible only in conditions of equal amount of the soil and dust in artificial mixtures, but this is impossible in natural conditions. It is necessary to find more senstive indicators of HM contamination for the investigated soils.